RELATION OF BODY MASS INDEX WITH LIPID PROFILE AND BLOOD PRESSURE IN YOUNG HEALTHY STUDENTS AT ZIAUDDIN MEDICAL UNIVERSITY - Aziz, Jawed; Siddiqui, Nadeem A; Siddiqui, Imran A; Omair, Amir (Journal of Ayub Medical College Abbottabad, 2003)
Background: This study was conducted to assess serum lipids in healthy young subjects in relation with their BMI. Methods: Students of Ziauddin Medical University were assessed for anthropometric measures, blood pressure and lipid profile at the time of their admission for MBBS program. Results: Out of 426 students all parameters were available for 301 students and they were selected for analysis in this study. Mean serum cholesterol in 301students was 149.3 ±31.3 mg/dl, mean LDL-C was 91.3 mg/dl ±27.7, mean HDL-C was 40.0 mg/dl ±42.2, mean triglycerides were 89.9 mg/dl ±42.2, mean systolic blood pressure was 113.1 mmHg ±13.5 and mean diastolic blood pressure was 74.0 mmHg ±8.1. The mean BMI of students was 21.6 Kg/m2 ±4.2. Among 301 students, 88 were underweight, 175 were normal and 38 were overweight according to their BMI. We found no significant difference in mean serum cholesterol and LDL-C while there were significant difference in mean serum HDL-C, triglycerides, systolic and diastolic blood pressure among the three BMI groups. Conclusion: In our study, there are high numbers of at-risk individuals. Therefore, strategies should be designed for weight reduction in children and adults to prevent cardiovascular disease. Keywords: Body Mass Index, Lipid Profile, Healthy students